Plant Regeneration of Malaysian Aromatic Rice MRQ88 Via Somatic Embryogenesis - Rahman, Zuraida Ab; Ramli, Asfaliza; Kamaruzaman, Rahiniza; Seman, Zulkifli Ahmad; Othman, Ayu Nazreena; Adlan, Nur Auni Syazalien; Basiron, Nur Najwa Arifah (European Journal of Applied Sciences, 2022)
Aromatic rice has become one of the most sought-after sources by today's consumers. As a result, by utilising mature seeds, an efficient somatic embryogenesis system for the MRQ88 variety has been constructed. Due to the highest percentage of callus initiation and no browning, MS-B5 medium supplemented with 1 mg/L 2,4-D and 10 mg/L NAA was the best medium for MRQ88 callus induction. Incubation of embryogenic callus on identical medium containing maltose 10 g/L and ABA 10 mg/L for 8 weeks resulted in the highest proportion of somatic embryo initiation (80%). The number of regenerated green plantlets on medium containing NAA and 2,4-D which was previously pre-treated with 5 to 10 mg/L ABA, 10 g/L maltose, showed good results, with 8-9 green plantlets developed.